Mikrotoponimia i ojkonimia gminy Uniejów - Prugar, Judyta (Biuletyn Uniejowski, 2014)
This article examines the linguistic aspect of names of places, both inhabited and uninhabited, within Uniejów commune. In total, 350 objects have been described. Information was obtained mainly through direct interviews with residents of the localities and from written sources. The article begins with explanations concerning proper names, toponyms and their classification model. It then presents a lexicon of all collected place names (oikonyms and microtoponyms) and discusses it, and provides a linguistic characterization of all the names according to the chosen classification model. The presented material can be useful in dialectological studies as many of the names have retained phonetic features specific to the local dialect. Names of geographical locations contained in this study are usually limited in range to single villages, in which they were created and transmitted from generation to generation or modified.